Studi Kepustakaan tentang Penerapan Model Discovery Learning dalam Meningkatkan Keterampilan Menulis Siswa pada Mata Pelajaran Bahasa Indonesia di Sekolah Dasar - Widya Asma Winda; Elfia Sukma (CV. ITTC INDONESIA, 2026)
This study aims to analyze the use of the Discovery Learning model in improving students’ writing skills in Indonesian language subjects at the elementary school level. The research was conducted using a literature study method by collecting various references, including books, scientific journals, and relevant previous studies. The data were analyzed using a descriptive qualitative approach to identify patterns and concepts related to the effectiveness of the model implementation. The findings indicate that Discovery Learning can help improve students’ writing abilities by encouraging them to be more active in generating ideas, developing concepts, and organizing their writing systematically. In addition, this model is also capable of fostering students’ creativity and independence in the learning process. Therefore, Discovery Learning can be considered an effective alternative learning model for enhancing elementary school students’ writing skills.